Will enhanced soldiers fight a just war? - Henschke, Adam (Australasian science, 2017)
[...]there is a case to be made for anthropological research in the military context, to get some idea of how those who we are fighting with understand the enhancements and what these different understandings mean in practice. [...]in terms of the ethics of such future technologies, we can take an approach that technology philosopher Philip Brey calls "anticipatory ethics for emerging technologies".